Phase Noise Spectrum of Microwave Active Ring Oscillators Based on Spin-wave Delay Lines - A. V. Drozdovskii; A. B. Ustinov; B. A. Kalinikos (Известия высших учебных заведений России: Радиоэлектроника)
A phase noise of microwave oscillators having an active ring circuitry with a spin-wave delay line is theoretically and experimentally investigated. The delay line was made with yttrium iron garnet (YIG) film epitaxially grown on gadolinium gallium garnet substrate. Obtained results demonstrate a management of the oscillator phase noise with a variation of the distance between antennas used for excitation and reception of spin waves in the YIG film.